Analysis of Income Inequality Between Regencies and Cities in Bengkulu - Anggara Putra Pratama; Damia Liana (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2025)
This study aims to analyze income disparities between districts and cities in Bengkulu Province and identify the influence of variables such as GRDP, population, and HDI on these income disparities. Income disparities are measured using the Williamson Index, while the factors influencing income disparities are analyzed using panel data regression methods with the assistance of EViews 12 software. Based on the results of the Chow test, Hausman test, and Lagrange Multiplier test, the random effect model was selected as the most appropriate model. The research results indicate that income inequality in Bengkulu Province is relatively low, influenced by differences in natural resources, human resources, and the allocation of development funds across regions. The regression analysis results show that the GRDP variable has a negative and significant effect on income inequality, while population size has a positive and significant effect on income inequality. On the other hand, the HDI also has a negative and significant effect, indicating that improving the quality of life through education and health can reduce income inequality. These findings support development theories that emphasize the importance of economic justice through improving the quality of human resources. Based on the results of this study, policies that support GRDP growth, population control, and HDI improvement are highly recommended to reduce income inequality in Bengkulu Province.